Principles of dealing with the changing world order why nations succeed and fail - Dalio, Ray. (London Simon & Schuster, 2021)
A few years ago, Ray Dalio noticed a confluence of political and economic conditions he hadn?t encountered before. They included huge debts and zero or near-zero interest rates that led to massive printing of money in the world?s three major reservecurrencies, big political and social conflicts within countries, especially the US, due to the largest wealth, political and values disparities in more than 100 years and the rising of a world power (China) to challenge the existing world power (US) and the existing world order. The last time that this confluence occurred was between 1930 and 1945. This realisation sent Dalio on a search for the repeating patterns and cause/effect relationships underlying all major changes in wealth and power over the last 500 years.